Effect of High-Tannin and -Polyphenol Plant Material Supplement on Rumen Fermentation, Nitrogen Partitioning and Nutrient Utilization in Beef Cattle - Pichad Khejornsart; Theerayut Juntanam; Pongsatorn Gunun; Nirawan Gunun; Anusorn Cherdthong (Animals)
The current issue of ruminant methane emissions is still being researched by animal nutritionists in an effort to find new approaches. In this study, five beef cattle were randomly assigned in a 5 × 5 Latin square design to examine the effects of supplementation with high-tannin and -polyphenol plant materials on nutrient utilization, rumen fermentation, and nitrogen partitioning. Cattle offered total mixed ration (TMR) silage diets with or without tannin-rich tree leaf or plant herbs, such as Piper sarmentosum Roxb., Cymbopogon citratus (DC.) Stapf, Anacardium occidentale L., and Careya arborea Roxb., were supplemented at a dose of 10 g/d. Prior to TMR feeding, the animals’ meals were supplemented with 10 g of fortified plant materials twice a day, along with 100 g of rice bran. The animals in the control group received only 100 g of rice bran and no other plant materials. The result showed that there was no difference in nutrient intake or digestibility between the supplemented and control groups. Although the effect of ruminal pH, NH3-N, Total VFA, acetate (C2), and butyrate (C4) was not significant (p > 0.05), the proportion of propionate (C3) tended to increase with supplementation (p = 0.07). There was no difference in the excretion of purine derivatives or the amount of microbial nitrogen supply, even though supplemented animals had significantly lower protozoal populations than the control group (p < 0.05). Moreover, when A. occidentale or C. arborea was added to the TMR silage diet, the nitrogen intake and retention increased considerably, although total nitrogen excretion decreased. In this approach, the leaves of Anacardium occidentale L. and Careya arborea Roxb. were particularly promising for strategic supplementation.